Interactive Da’wah Communication of Ustadz Syam on TikTok - Mochammad Irfan Achfandhy; Mutiara Rizqa Chairunnisa (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
TikTok is a da'wah communication medium for preachers containing content related to religious teachings. Each da'wah content receives various responses and reflects an interactive communication model. Thus, this study aims to investigate the interactive communication model within religious preaching on TikTok. The study focuses on the responses of internet users to the religious leader Ustadz Syam's content, as featured on his TikTok account @syam_elmarusy. The primary data was gathered using a qualitative approach, employing the netnography method. The content analysis method with the interactivity theory was used for analysis. The findings suggest that interactivity in religious preaching on TikTok can be divided into three categories: user-to-system interactions (such as likes, views, and subscribers), user-to-user interactions (such as comments from internet users), and user-to-document interactions (such as sharing content with other users). The results illustrate the interconnected pattern of interactivity between internet users, the content creator, and the TikTok platform, where all parties reinforce and complement each other.